Generation of tumor‐specific cytotoxic T‐lymphocytes from the peripheral blood of colorectal cancer patients for adoptive T‐cell transfer. Issue 7 (July 2015) - Carluccio, Silvia; Delbue, Serena; Signorini, Lucia; Setola, Elisabetta; Bagliani, Anna; Della Valle, Alberto; Galli, Andrea; Ferrante, Pasquale; Bregni, Marco
Abstract : This study designs a strategy for an adoptive cellular therapy (ACT) protocol based on the ex‐vivo selection of autologous peripheral blood‐derived CD8‐enriched T‐cells, stimulated with dendritic cells (DCs) that had been pulsed with apoptotic tumor cells to generate cytotoxic T lymphocytes (CTLs) with anti‐tumor activity. Seventy‐eight colorectal cancer (CRC) patients were enrolled in this study. Tumor tissues and peripheral blood (PB) were obtained at surgery. Tissues were mechanically dissociated and cultured to obtain a primary tumor cell line from each patient. DCs were derived from peripheral blood mononuclear cells (PBMCs) using magnetic positive selection of CD14+ monocytes. Anti‐tumor CTLs were elicited in co‐/micro‐cultures using DCs as antigen‐presenting cells, autologous apoptotic tumor cells as a source of antigens, and CD8+ T lymphocytes as effectors. Interferon‐γ (IFN‐γ) secretion was assessed by ELISpot assays to evaluate the activation of the CTLs against the autologous tumor cells. Primary tumor cell lines were obtained from 20 of 78 patients (25.6%). DCs were generated from 26 patients, and of them, corresponding tumor cell lines were derived from six patients. ELISpot results showed that significant IFN‐γ secretion was detected after different numbers of stimulations for two patients, whereas weak secretion was observed for three patients. Despite difficulties due to contamination of several primary tumor cell lines with gut intestinal flora, the results suggest that the generation of tumor‐specific CTLs is feasible from patients with CRC, and could be useful for supporting an ACT approach in CRC. J. Cell. Physiol. 230: 1457–1465, 2015. © 2015 Wiley Periodicals, Inc., A Wiley Company